Lubok 6 - Ruckhäberle, Christoph; Siemon, Thomas (Leipzig : Lubok Verlag, 2008)
Christian Brandl, Hubert Becker, Thomas Gosebruch, Stephen Cambers, Johannes Eckardt, Stephanie Marx, Frank Wahle, Herbert Klee, Tim von Veh
Exemplar No.: 001/700
boek